The transillumination technique as a method for the assessment of spermatogenesis using medicinal plants: The effect of extracts of black maca (Lepidium meyenii) and camu camu (Myrciaria dubia) on stages of the spermatogenic cycle in male rats - Gonzales G.F. (2013)
This study was supported by a grant obtained from the Peruvian National Council of Sciences, Technology and Innovation (CONCYTEC) through the grant PROCOM 2009, No. 217-2009, Peru. G. F. participated in the design of the study and writing the paper. B. V. V. and M. G. participated in the development of the study. All the authors revised the manuscript. Dr. Gustavo F. Gonzales is in charge of CAYENATUR EIRL, a small enterprise that develops products based on maca. No other authors have conflict of interest.